Endocrine-Immune Interactions in Pregnant Non-Human Primates With Intrauterine Infection - Michael G. Gravett; Miles J. Novy (Hindawi Limited, 1997)
Preterm birth remains the most common cause of perinatal mortality. Although the causes of preterm labor are multifactorial and vary according to gestational age, preterm labor and term labor share common cellular and molecular mechanisms, including stimulation of the fetal hypothalamic-pituitary-adrenal (HPA) axis and endocrine/immune system interactions. We have developed a non-human primate experimental model for intrauterine infection and preterm labor using chronically instrumented rhesus monkeys (Macaca mulatta) with timed gestations. We have documented the temporal and quantitative relationships among intrauterine infection, the synthesis and release of proinflammatory cytokines, prostaglandins, and fetal-placental steroid biosynthesis in this model. Infection-induced preterm parturition is characterized by significant elevations in amniotic fluid proinflammatory cytokines and by increases in fetal adrenal steroid biosynthesis, but not by corresponding increases in placental estrogen biosynthesis characteristic of spontaneous parturition. This suggests that activation of the fetal HPA axis by the stress of infection is accompanied by placental dysfunction and also that infection-induced preterm parturition is not dependent upon the increased estrogen biosynthesis observed in spontaneous parturition. These different endocrine and immune responses have important diagnostic and therapeutic implications in the management of preterm labor.